2019
DOI: 10.5194/cp-2019-60
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OPTiMAL: A new machine learning approach for GDGT-based palaeothermometry

Abstract: Abstract. In the modern oceans, the relative abundances of Glycerol dialkyl glycerol tetraether (GDGTs) compounds produced by marine archaeal communities show a significant dependence on the local sea surface temperature at the site of formation. When preserved in ancient marine sediments, the measured abundances of these fossil lipid biomarkers thus have the potential to provide a geological record of long-term variability in planetary surface temperatures. Several empirical calibrations have been made betwee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…If BAYSPAR is used, we recommend that researchers report the parameters used (the prior mean and standard deviation, the search tolerance, and the version of the calibration dataset) so that the results are reproducible. The issue of extrapolation beyond the temperature range of the modern GDGT calibration dataset is highlighted in Eley et al (2019), which also proposes an alternative calibration methodology.…”
Section: Recommended Methodologies For Tex 86mentioning
confidence: 99%
See 1 more Smart Citation
“…If BAYSPAR is used, we recommend that researchers report the parameters used (the prior mean and standard deviation, the search tolerance, and the version of the calibration dataset) so that the results are reproducible. The issue of extrapolation beyond the temperature range of the modern GDGT calibration dataset is highlighted in Eley et al (2019), which also proposes an alternative calibration methodology.…”
Section: Recommended Methodologies For Tex 86mentioning
confidence: 99%
“…Whilst some uncertainty may be alleviated by comparison with associated multiproxy data (e.g., Frieling et al, 2017;Tierney et al, 2017), TEX 86 values > 0.8 require extrapolation of the relationship between TEX 86 and temperature beyond the modern calibration dataset or incorporation of limited data from laboratory studies (e.g., Pitcher et al, 2009;Elling et al, 2015). Such high values almost certainly indicate hotter temperatures, but the degree of estimated warming depends on assumptions about the mathematical nature of the temperature-TEX 86 relationship (see below and discussion in Eley et al, 2019). C. J. Hollis et al: The DeepMIP contribution to PMIP4…”
Section: Weaknesses Of Tex 86mentioning
confidence: 99%
“…The DeepMIP database excludes samples with anomalous GDGT distributions (Hollis et al, 2019). However, a Gaussian pro-cess regression (GPR) model may help to better identify anomalous GDGT distributions in the sedimentary record using a nearest-neighbour distance metric (Eley et al, 2019). This methodology could be employed in future studies to further refine GDGT-based SST datasets, but this methodology is currently under review and is not considered here.…”
Section: Influence Of Different Proxy Datasets Upon D Surf -Derived Gmentioning
confidence: 99%
“…Recent culture studies (Elling et al, 2015) have found that there is not a common linear TEX 86 response to growth temperature in cultivated strains of Thaumarchaeota. Eley et al (2019) recently applied machine-learning tools (e.g., Gaussian Process Emulators) to the isoGDGT global calibration dataset and found a strong, underlying temperature-dependence, but also highlighted how fossil GDGT distribution patterns differed significantly from the modern especially in the Eocene and Cretaceous. Finally, the LDI index, derived from diols produced by microalgae, has been applied to reconstruct SSTs throughout the Quaternary (Naafs et al, 2012;Rodrigo-Gámiz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%